AN ANALYSIS OF IMPACT OF EVIDENCE BASED LEARNING ON ACADEMIC ACHIEVEMENT OF STUDENTS - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2020)
The outcome-based learning is leading and has set a new trend in innovative class-room instructions. In Chemistry, the solid-state structures and composite materials are covered in classroom due to its use in day to day life. In this paper attempt is made to present novel handmade model as a tool that provides a desired link between the unit cell representation and extended structure. This model offers visualization stacking pattern that provides simple- unit cell, body- centered and face -centered cubic and hexagonal closed packed cell. Preparing and using molecular handmade model in Teaching-Learning is significant and has a positive impact on academic achievement. The students handmade models acts as a tool for teaching and it has considerable importance in Science education. Totally 40 students of Grade 12 are selected as the sample for the present study. Students are divided into two sets - experimental group and control group. Each group consists of 20 students. Students of the experimental group are asked to make handmade model of unit cells. This handmade model of cells and pieces combines into three corresponding crystal shapes and through this students are taught about the primitive cell of solid state. The control group is taught by using traditional chalk and talk method. The present study is experimental in nature. The pre-test and post-test equivalent group design is used for collecting data. The mean deviation and difference of mean are computed for both groups. The significant differences of both the experimental and the control group based on the variables of pre-test and post-test are tested at 0.05 level by applying t-test. On the completion of statistical analysis of data and research it is concluded that the handmade model of the primitive cells of solid state unit of Chemistry has significant positive effect on the academic achievement of the students in Chemistry at Senior Secondary School level. Based on the findings it is recommended that teachers should use outcome based Teaching-Learning approach to move up student’s achievement in core subjects.